2017
DOI: 10.1111/1750-3841.13964
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Flaxseed Oil and Flaxseed Lignan Secoisolariciresinol Diglucoside Against Oxidative Stress in Rats with Metabolic Syndrome

Abstract: We report that the antioxidant effects attributed to flaxseed are mainly due to its high lignan content, especially that of secoisolariciresinol diglucoside. This is significant because suggests that this compound can be used in isolation to prevent oxidative stress associated with MS. Furthermore, this study was the only one to perform a comparison of the abilities of 2 components of flaxseed to protect against oxidative stress in an MS model, which brings a great advance in the medicine's field, since it ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 48 publications
(55 reference statements)
3
37
0
Order By: Relevance
“…It is reported that fructose administration induces hepatic oxidative stress by inflammatory and metabolic changes. Fructose consumption increased PCO and MDA levels and, decreased GSH level . Haj et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is reported that fructose administration induces hepatic oxidative stress by inflammatory and metabolic changes. Fructose consumption increased PCO and MDA levels and, decreased GSH level . Haj et al .…”
Section: Discussionmentioning
confidence: 97%
“…Fructose consumption increased PCO and MDA levels and, decreased GSH level. [23,34] Haj et al [35] reported that a novel non-psychotropic cannabinoid HU-444 by increased doses was inhibited the ROS level on macrophages. Vella et al [36] showed that STZ-induced increased MDA levels were decreased by THC.…”
Section: Discussionmentioning
confidence: 99%
“…on oxidative stress [9,10]. Recently, flaxseed has been promoted as a functional food due to its health benefits, which are mainly attributable to its high omega-3 fatty acid, lignan, dietary fiber and antioxidant contents [11][12][13][14][15]. The protective role of flaxseed oil against oxidative stress in metabolic syndrome has been documented in a murine model [14].…”
mentioning
confidence: 99%
“…Recently, flaxseed has been promoted as a functional food due to its health benefits, which are mainly attributable to its high omega-3 fatty acid, lignan, dietary fiber and antioxidant contents [11][12][13][14][15]. The protective role of flaxseed oil against oxidative stress in metabolic syndrome has been documented in a murine model [14]. The beneficial effect of flaxseed supplementation on amelioration of central obesity and reduction of insulin resistance is also documented [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation